High-energy and fast-charging lithium metal batteries enabled by tuning Li+-solvation via electron-withdrawing and lithiophobicity functionality - Guangzhao Zhang; Tong Zhang; Zhen Zhang; Ruilin He; Qingrong Wang; Shang-Sen Chi; Yanming Cui; Meng Danny Gu; Zhongbo Liu; Jian Chang; Chaoyang Wang; Kang Xu; et al. (Nature Communications)
Abstract The solvent fluorination almost always improves electrochemical stability of electrolytes against both lithium anodes and high-voltage cathodes in lithium metal batteries. However, how exactly fluorination affects Li+-solvation and interphasial chemistries remains unclear, hindering rational design of electrolytes and interphases with both wide electrochemical stability window and fast ion transport kinetics that are required for energy-dense and fast-charging LMBs. Here we introduce the trifluoromethylation (-CF3) at one end of 1,2-dimethoxyethane and generate 1,1,1-trifluoro-2-(2-methoxyethoxy) ethane, which as a single solvent of electrolyte simultaneously meets energy-dense and fast-charging requirements when dissolving 2 M lithium bis(fluorosulfonyl)imide. Beside the electron-withdrawing effect of -CF3, we find that its lithiophobic nature against Li+ significantly alters the solvation structures, which favors the formation of anion-dominated clusters that lead to superior interphasial chemistries in layered structure and fast Li+ transport kinetics. In such electrolyte, lithium metal batteries constructed with 50-μm-thin Li||high-loading-NMC811 in both coin and pouch cell configurations achieve >400 cycles under fast-charging condition, and >100 cycles in 14-Ah-level industrial pouch cell with a high energy density over 510 Wh kg−1 at cell-level.